Explorations of miRNA expression in the mammalian retina - Loscher, Carol Jane (Trinity College (Dublin, Ireland). Department of Genetics, 2009)
MicroRNAs (miRs) are an abundant class of non-coding RNAs which, for the most part were undiscovered until early this decade (Lagos-Quintana et al. 2001; Lee et al. 2001). Mature miR transcripts are small (~22 nucleotides) RNAs that control eukaryotic gene expression at the post-transcriptional level by interacting with target mRNAs, which either results in mRNA cleavage or translational repression (Bartel 2004). Tissue-specific expression of miRs is well documented, however, a clear understanding of the functions of the majority of miRs remains elusive. MiRs are known to participate in a wide range of developmental and physiological processes, and perturbed miR expression has been shown to occur in cancer and other diseases (Alvarez-Garcia et al. 2005; Bandres et al. 2006). This Ph.D. thesis describes the exploration of retinal miR expression and possible involvement of miRs in retinal disease, specifically in the mouse models of retinitis pigmentosa (RP). RP is a group of inherited retinal degenerations which leads to blindness typically by middle age, due to the loss of rod and cone photoreceptors which die by apoptosis. The primary genetic cause for many forms of RP have been identified. Characterising the miR expression profile in the retina is essential to elucidate miR involvement in retinal-specific functions and Chapter 3 describes the examination of miR expression in the mouse retina by microarray analysis, in comparison to other brain and other tissues. Specifically a number of miRs are identified which are preferentially expressed in the retina, suggesting that these miRs may possibly be involved in regulating retinal-specific functions.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin